Synthesis and modification of silica‐based epoxy nanocomposites with different sol–gel process enhanced thermal and mechanical properties. Issue 40 (27th May 2021) - Aziz, Tariq; Mehmood, Sahid; Haq, Fazal; Ullah, Roh; Khan, Farman Ullah; Ullah, Bakhtar; Raheel, Muhammad; Iqbal, Mudassir; Ullah, Asmat
Abstract: This research article describes the results of nano‐silica composites filled with different epoxy contents containing nano‐SiO2 particles from (5–25 wt%). Reinforcing hybrid composites enhance thermal and mechanical properties to achieve vital and sustainable products. Silica‐based nanocomposites with high purity were prepared and used for the surface modification of nanosized silica particles. The surface structure's composition and physical properties of modified nano‐SiO2 particles were characterized through Fourier transferred infrared spectrometer, X‐ray photoelectron spectroscopy, thermogravimetric analyzer, and scanning electron microscopic. Silica‐based nanocomposites were prepared by incorporating of modified nano‐SiO2 as an enhancing filler. The morphology of fracture surface and dynamic mechanical properties were investigated. Results showed that the silica‐based epoxy nanocomposites are bearing a long chain structure that could improve the compatibility of silica nanocomposites with epoxy resin and contribute to a better dispersion state in the matrix, which enhanced the overall performance of epoxy‐cured products. Abstract :